Brief considerations on Promissory note: notion and characteristics, function and importance, classification and extinction - Pacheco, Fátima (Revista Jurídica Portucalense, 2019)
The present study results from the experience of a few years of teaching in the discipline of Business Law and responds to the need to create a text, simple and concise, that serves as a study base for students of the Institute of Accounting and Administration of Porto. The work that now comes to light only focuses on Promissory note. Since this is very similar to the Bill of Exchange, the study of the general characteristics of the debt securities, the exchange legal relationship and the foreign exchange business applicable to it - prior to the study of Promissory Note - makes it possible to understand the generality of its legal regime. In fact, it finds its discipline in Promissory Note the same law that governs the Letter, in particular in the articles 75 to 78, and by virtue of art. 77, refers almost entirely to the letter. The work has chosen not to present doctrinal debates and aims to contribute to understanding the economic function assumed by this legal instrument, as well as the virtualities that it contains. It is true that protection of the good faith of third-party purchasers and the speed of movement requires simplicity in their transmission and that, as well as permitting the mobilization of the credits which they incorporate, they constitute an enforceable instrument which can to the collection of the assets and / or income of the debtor - the text intends to record the typical moments of the legal regime of Promissory Note.